EKSPLORASI KESEDIAAN MEMBAYAR PARKIR MAHASISWA MENGGUNAKAN STATED PREFERENCE SURVEY METHOD - Rizki, Muhamad; Kosakoy, Chrisma Merry; Joewono, Tri Basuki (FSTPT Indonesia, 2015)
Fare determination is one of the strategies in transportation management in campus area especially to solve parking problem. This study aims to find the value of the willingness to pay of student for using parking facilities based on parking duration and quality of facilities. Analysis shows that there is significant different in the average of WTP for different group of parking quality. This study also found that the characteristics of travel and activities influence the value of WTP, where it is not only influenced by economic capability. Student who are young and more active in conducting travel tends to show higher willingness to pay.